The Burden of Dengue and Chikungunya Worldwide: Implications for the Southern United States and California - Anthony C. Fredericks; Ana Fernandez-Sesma (Ubiquity Press, 2015)
Background: Dengue virus (DENV) spreads to humans through the bite of an infected 'Aedes aegypti' or 'Aedes albopictus' mosquito and is a growing public health threat to both industrialized and developing nations worldwide. Outbreaks of autochthonous dengue in the United States occurred extensively in the past but over the past 3 decades have again taken place in Florida, Hawaii, and Texas as well as in American Samoa, Guam, Northern Mariana Islands, Puerto Rico, and the US Virgin Islands. As the 'Aedes' vectors spread worldwide it is anticipated that DENV as well as other viruses also transmitted by these vectors, such as Chikungunya virus (CHKV), will invade new areas of the world, including the United States. Objectives: In this review, we describe the current burden of dengue disease worldwide and the potential introduction of DENV and CHKV into different areas of the United States. Of these areas, the state of California saw the arrival and spread of the 'Aedes aegypti' vector beginning in 2013. This invasion presents a developing situation when considering the state's number of imported dengue cases and proximity to northern Mexico as well as the rising specter of chikungunya in the Western hemisphere. Findings: In light of the recent arrival of 'Aedes aegypti' mosquito vectors to California, there is now a small but appreciable risk for endemic transmission of dengue and chikungunya within the State. It is likely, however, that if DENV or CHKV were to become endemic that the public health situation would be similar to that currently found along the Texas-Mexico border. The distribution of 'Aedes' vectors in California as well as a discussion of several factors contributing to the risk for dengue importation are discussed and evaluated. Conclusions Dengue and chikungunya viruses present real risks to states where the 'Aedes' vector is now established. Scientists, physicians, and public health authorities should familiarize themselves with these risks and prepare appropriately.